The influence of soil types and agricultural management practices on soil chemical properties and microbial dynamics - Poonia, Tanuja; Choudhary, Madhu; Kakraliya, Manish; Dixit, Bharti; Jat, Hanuman Sahay (Frontiers in Sustainable Food Systems, 2024)
Soil provides essential nutrients for plant growth, but excess salts hinder development, making crops more vulnerable under climate change conditions. Soil microorganisms play a significant role in nutrient cycling. However, limited information is available on microbial behavior/community changes, and functional diversity in different soil types (normal, sodic, and highly sodic) and cropping systems [rice-wheat (RW); rice-wheat-mungbean (RWMb); maize-wheat-mungbean (MWMb)] and management practices in the north-western Indo-Gangetic Plains of India. We investigated the influence of different soil types on physical and chemical properties at the surface level (0–15 cm) in relation to soil microbial population, activities, and functional diversity, focusing on community-level physiological profiling (CLPP) under different agriculture systems. Seven treatment combinations of soil types, cropping systems, and management practices were evaluated. Soil pHs were found to be lower in zero-till (ZT)-based sodic soil than in conventional-till (CT) sodic soil. Soil organic carbon (SOC) (0.91 and 0.90%) content and available N (154.46 and 132.74 kg ha−1) were higher with the ZT-based system under normal (N) soils (ZT-RWMb-N and ZT-MWMb-N) than in CT-based normal soil (0.67 and 121.04 kg ha−1). Similarly, higher SOC and N (0.85 and 76.11 kg ha−1) were found under ZT management in sodic soils (S) than under CT management (0.73% and 121.05 kg ha−1). Substrate utilization (amino acids, amines, carbohydrates, carboxylic acids, phenolic compounds, and polymers) increased with the incubation period. During 0–120 h of incubation, the highest utilization of amino acids, amines, carboxylic acids, phenolic compounds, and polymers was observed for ZT-MWMb-S soils, while the lowest was recorded for ZT-MWMb-N soils. Under high salt conditions, soil enzymatic activities (dehydrogenase, acid phosphatase, alkaline phosphatase, etc.) declined significantly compared to normal soils, affecting soil chemical and physical conditions. Microbial population and enzyme activities decreased with increasing salt stress across all cropping systems. These findings suggest that adopting efficient crop management practices can help mitigate the adverse effects of soil salinity on microbial diversity and soil health, thereby enhancing sustainable agricultural productivity in salt-affected regions.